An experimental study on restoration technique for the Acropolis of Athens: developing the experimental set-up for pull-out testing of titanium bars embedded in marble blocks (Fracture and Structural Integrity, 2019)
This work aims at investigating the mechanisms activated during the extraction of titanium bars from a marble volume (pull-out phenomenon), used for rejoining fragmented marble structural members at the monuments of the Acropolis of Athens. The restoration protocol includes the insertion of threaded titanium bars into pre-drilled holes in the body of the structural members. The adhesion between marble and bars is achieved by an initially liquid cementitious material. There are two main aspects on which this project focuses. Firstly, the weak link of the marble-cement-titanium complex, the marble-cement interface, is inaccessible for traditional sensing techniques. In this context, the Acoustic Emission technique is employed in order to detect failure and damages at the interior of the complex. Secondly, the specimens and the experimental procedure should simulate the same stress conditions in which all three phases within the marble-cement-titanium complex are under, while the structural member is in service. For this purpose, two modified tests are proposed aiming at efficiently simulating the bars’ behavior as they are sliding through a marble epistyle. These tests provide promising results with regards to keeping the examined surface between bars and marble free from parasitic stresses caused by the experimental set-up.
Keywords: Marble; Stone monuments; Pull-out; Restoration; Contact interfaces; Acoustic Emission